The Effect of Weighted Ball Shooting Training on Shooting Improvement in Female Basketball Athletes - Virna Sabrina Diaz; Alen Rismayadi; Masayu Rizka Risjanna (Universitas Negeri Semarang, 2025)
This study aimed to examine the effect of weighted ball shooting training on the improvement of shooting skills in female basketball athletes. An experimental approach employing a One Group Pretest–Posttest Design was applied. The research participants consisted of 12 female basketball athletes aged 18 years from the Favorita KU Club. Total sampling was used, meaning all members of the population were included as the research sample. Shooting performance was measured using the Shooting Point Test. Data were analyzed using a Paired Sample T-Test with SPSS version 26. The findings indicated that the weighted ball shooting training model significantly enhanced the shooting skills of the basketball athletes, with an improvement of 27.95%. The results of the study indicate that the weighted ball shooting training model had a significant effect on improving basketball athletes’ shooting performance. The conclusion is that weighted ball shooting training is effective in improving shooting performance in female basketball athletes. The implementation of a five-week training program with a repetition-based approach resulted in a statistically significant improvement in shooting ability.